2018
DOI: 10.1186/s13068-018-1317-3
|View full text |Cite
|
Sign up to set email alerts
|

Dual expression of plastidial GPAT1 and LPAT1 regulates triacylglycerol production and the fatty acid profile in Phaeodactylum tricornutum

Abstract: BackgroundMetabolic engineering has emerged as a potential strategy for improving microalgal lipid content through targeted changes to lipid metabolic networks. However, the intricate nature of lipogenesis has impeded metabolic engineering. Therefore, it is very important to identify the crucial metabolic nodes and develop strategies to exploit multiple genes for transgenesis. In an attempt to unravel the microalgal triacylglycerol (TAG) pathway, we overexpressed two key lipogenic genes, glycerol-3-phosphate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 58 publications
3
37
1
Order By: Relevance
“…In our previous study, we identified GPAT1 in P. tricornutum, which resulted in a significant elevation of neutral lipids by two-fold [6]. Similarly, dual overexpression of GPAT1 and LPAT1 resulted in a 2.3-fold increment in neutral lipids in P. tricornutum [9]. Previous report has shown that each isoform of GPAT exhibit crucial lipogenic role in mammals [27].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In our previous study, we identified GPAT1 in P. tricornutum, which resulted in a significant elevation of neutral lipids by two-fold [6]. Similarly, dual overexpression of GPAT1 and LPAT1 resulted in a 2.3-fold increment in neutral lipids in P. tricornutum [9]. Previous report has shown that each isoform of GPAT exhibit crucial lipogenic role in mammals [27].…”
Section: Discussionmentioning
confidence: 84%
“…Nevertheless, lipid metabolism in microalgae is complex in nature due to the presence of regulatory factors at various levels, thereby enabling them recalcitrant to metabolic engineering [26]. Consequently, various previous studies have devoted tremendous research efforts to metabolically engineer oleaginous algal species, and studies showed that engineering the TAG pathway has resulted in promising results in microalgae [6,7,9,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous report has shown that overexpression of plastidial LPAAT elevated saturated and polyunsaturated fatty acids, and decreased monounsaturated fatty acids with particular increment and decrement of C16:0 and C16:1 fatty acids, respectively . Similarly, dual overexpression of plastidial GPAT and LPAAT resulted in remarkable lipid enhancement with an altered fatty acid profile in Phaeodactylum tricornutum (Wang et al, 2018). In addition, DGAT, which catalyzes the final committed step of TAG biosynthesis, was remarkably increased during the late growth phase.…”
Section: Prokaryotic Tag Biosynthetic Pathway Could Be the Master Regmentioning
confidence: 96%
“…In this respect, the genetic and metabolic engineering of microalgae are being actively pursued to improve lipid production, which can contribute to reduced biofuel prices [6][7][8][9]. Strain development has focused on the overexpression of metabolic enzymes related to lipid biosynthesis [10][11][12][13][14] and transcriptional regulators [15][16][17][18], or the targeted mutagenesis of competitive pathways of lipid biosynthesis using TALEN, RNAi, and CRISPR/Cas9 techniques [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%